2013
DOI: 10.1097/hjh.0b013e328364103f
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of clinic and ambulatory blood pressure components in high-risk type 2 diabetic patients

Abstract: ABPM provides more valuable information regarding cardiovascular risk stratification than office BPs and should be performed, if possible, in every high-risk type 2 diabetic patient. Achieved 24-h ambulatory BPs less than 120/75 mmHg are associated with significant cardiovascular protection and, if confirmed by other studies, may be considered as BP treatment targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 40 publications
1
57
1
1
Order By: Relevance
“…The characteristics of this cohort, the baseline procedures and the diagnostic definitions have been detailed elsewhere [15,[18][19][20]. In brief, the inclusion criteria were all adults with type 2 diabetes who were aged up to 80 years and had either any microvascular (retinopathy, nephropathy or neuropathy) or macrovascular (coronary, cerebrovascular or peripheral artery disease) complication, or at least two other modifiable cardiovascular risk factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of this cohort, the baseline procedures and the diagnostic definitions have been detailed elsewhere [15,[18][19][20]. In brief, the inclusion criteria were all adults with type 2 diabetes who were aged up to 80 years and had either any microvascular (retinopathy, nephropathy or neuropathy) or macrovascular (coronary, cerebrovascular or peripheral artery disease) complication, or at least two other modifiable cardiovascular risk factors.…”
Section: Methodsmentioning
confidence: 99%
“…The diagnostic criteria for chronic complications of diabetes have previously been detailed [15,[18][19][20]. Briefly, CHD was diagnosed by clinical electrocardiographic criteria or by positive ischaemic stress tests.…”
Section: Methodsmentioning
confidence: 99%
“…All were submitted to a standard baseline protocol that included a complete clinical examination, laboratory evaluation, and cf-PWV measurement. Diagnostic criteria for chronic diabetes complications have previously been described (9,(24)(25)(26). Specifically for this analysis, patients with aorto-iliac occlusive disease were excluded because of its effect on pulse wave velocity measurement (26).…”
Section: Patients and Baseline Proceduresmentioning
confidence: 99%
“…All participants gave written informed consent, and the local ethics committee had previously approved the study protocol. The characteristics of this cohort, the baseline procedures, and the diagnostic definitions have previously been described (9,(24)(25)(26). In brief, subjects included were all adults with type 2 diabetes up to 80 years old either with any microvascular (retinopathy, nephropathy, or neuropathy) or macrovascular (coronary, cerebrovascular, or peripheral artery disease) complication or with at least two other modifiable cardiovascular risk factors.…”
Section: Patients and Baseline Proceduresmentioning
confidence: 99%
“…36 Moreover, a recent study in high-risk patients with type 2 diabetes mellitus reported significantly more CV events for an achieved nighttime SBP ≥120 mm Hg compared with nighttime SBP <110 mm Hg. 37 Interestingly, from the data of the MAPEC study, 8 lower CV risk was found with the progressive reduction in achieved asleep SBP, irrespective of administration time of antihypertensive drugs. 38 Thus, for both dosing regimens CV risk was lowest in patients with achieved asleep SBP <103 mm Hg and significantly higher when >115 mm Hg.…”
Section: Discussionmentioning
confidence: 99%